FORMAL SCIENCE COMMUNICATION IN THE RESEARCH PAPERS “KNYGOTYRA” AND “INFORMACIJOS MOKSLAI”: QUANTITATIVE ANALYSIS - STONKIENĖ, MARIJA; JANIŪNIENĖ, ERIKA; MATKEVIČIENĖ, RENATA (Knygotyra, 2010)
For intensive academic activities, there is a need to ensure introduction of scientific research results, discussion of scientific works and spread of scientific investigation results in an interaction among scientists, scientists and scientific community, scientists and society. This kind of communication creates and fosters the persistent value of scientific work through the presentation and dissemination of results of scientific theoretical and empirical investigations. In the article, scientific communication is understood as a dissemination of scientific information of all areas of scientific research through formal and informal channels of communication. Scientific communication as a concept unites various possibilities such as science mass communication, public understanding of science, public awareness of science, scientific culture, scholarly communication aspects such as academic communication, purely scientific communication, etc. The aim of the article is to analyze formal science communication presented by scientists from the Faculty of Communication of Vilnius University. The research aims to present completeness of science communication presented by the scholars of the Faculty of Communication in dissemination of results of scientific researches and to create a knowledge dissemination map in which a flow of science communication and activities of scholars could be shown. The research is based on the quantitative variables that describe the form of science communication, from analysis of documental communication in scientific publications to formal communication such as participation in national and international conferences, expert activities, etc. Analysis of formal science communication is carried out from four main points: analysis of the science communication structure at the Faculty of Communication, Vilnius University; measurement of the geographical scope of science communication performed by the scholars of the Faculty; a set of participants and a flow of science communication; identification of institutions and individual scholars that actively participate in science communication in the field of communication and information. Results of the research stress several important aspects which present science communication at the Faculty of Communication of Vilnius University: the communication model “scientists to scientists” is dominating; dissemination of scientific information is oriented towards the Lithuanian scientific community; by active participation in international scientific networks and conferences; the map that presents the spread of scientific research results is wider than Lithuania’s geographical frame. As the main means for formal science communication, scientific publications could be mentioned. “Knygotyra” and “Informacijos mokslai” are the main scientific journals where formal science communication in the area of communication and information is concentrated.